Pengaruh Label Halal, Citra Merek, dan Online Consumer Review terhadap Keputusan Pembelian Kosmetik Wardah - Amin, Mia Adisty; Rachmawati, Lucky (Jurnal Ekonomika dan Bisnis Islam, 2020)
Cosmetics are one of the needs of women to support their appearance, especially a muslim woman who want to look beautiful without having worry about the provisions of islam. The development of cosmetic industry is growing rapidly to innovate and accept the challenges. The purpose of this research to determine the simultaneously effect of halal label, brand image, and online consumer review on purchasing descision of Wardah Cosmetics. The sample is 100 muslim women respondents who have used or bought Wardah cosmetics in Surabaya. Data collection methods used in this research was a likert scale questinnaire. Data analysis techniques usedare the instrument test, multiple linear regression, and hypothesis test. The results of this research are halal label and brand image significantly influences purchasing decision,while online consumer review doesnt significantly influence Wadah cosmetics purchasing decisions.